Démarche d’intervention sur l’organisation du travail afin d’agir sur les problèmes de santé mentale au travail - Louise St-Arnaud; Sylviane Gignac; Pierre Gourdeau; Mariève Pelletier; Michel Vézina (Perspectives Interdisciplinaires sur le Travail et la Santé)
Mental health problems in the workplace currently represent a public health and major economic problem. While the pathogenic impact of certain dimensions of work organization on mental health has been widely documented, research on the identification of effective strategies for reducing these constraints has not been extensively developed. Founded on an intervention framework of a participatory work organization process, a group of practitioners and researchers in mental health in the workplace tested the proposed process on several occasions, by integrating a continuous evaluation process into it. Each step in the process was reviewed by considering the actions and methods used, and by taking into account the preventionists’ experience as well as the observations in the interventions being pursued. What the workplace experiments and the literature revealed was used to modify, improve or define the intervention process. This article presents in detail each of the steps in a preventive intervention process in mental health in the workplace, revised by a continuous testing and evaluation process.